SESQUITERPENE LACTONES WITH ANTIBACTERIAL ACTIVITY FROM TANACETUM-DENSUM SUBSP SIVASICUM - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
The aerial parts of Tanacetum densum subsp. sivasicum yielded, in addition to known compounds, a new sesquiterpene lactone, sivasinolide which showed antibacterial activity against Bacillus subtilis and Klebsiella pneumoniae. The structures were elucidated by spectral methods. Some sesquiterpene lactones were evaluated for their cytotoxic activity.
Keywords: TANACETUM-DENSUM SUBSP SIVASICUM; COMPOSITAE; TRITERPENOIDS; AROMATIC COMPOUNDS; FLAVONOIDS; SESQUITERPENE LACTONES; EUDESMANOLIDES; GERMACRANOLIDES; GUAIANOLIDES; ANTIBACTERIAL ACTIVITY; CYTOTOXICITY; OCCURRING TERPENE DERIVATIVES